Analisis Penerapan Manajeman Risiko Dalam Upaya Peningkatan Keselamatan Pasien Di Rsud Al Ihsan Provinsi Jawa Barat - Ratnasari, Dewi; Ariyani, Nurul Dwi (Barongko: Jurnal Ilmu Kesehatan, 2024)
This research aims to find out how risk management is implemented in Al Ihsan Regional Hospital, identify hazards affecting patient safety in Al Ihsan Regional Hospital, analyze the risk list in Al Ihsan Regional Hospital and find out what efforts are being made, to improve patient safety. Al-Ihsan Regional Hospital. This research is also expected to expand the author's knowledge and experience. This research uses qualitative research methods. Two types of data sources used in this research are primary data and secondary data. This research collects data through uninvolved observation. If the observer acts only as an independent observer and is not directly involved, the observer is considered not involved. In addition to observation, the author of this study also used literature studies to collect data. The research results show that Al Ihsan Regional Hospital Implementation of risk management by the quality committee to identify, analyze and control various risks that may arise in hospital operations. In addition to the quality committee, the manager's role in motivating staff and all hospital units also has a major impact on the implementation of effective risk management. Improving the safety culture in hospitals to protect patients and improving healthcare services are two important parts of this risk management. This process also includes establishing the hospital's risk profile and developing effective control strategies to minimize incidents that could potentially harm patients. This study highlights the importance of good collaboration and consistent implementation of control strategies to improve patient safety and maintain hospital operational efficiency.